BMI but not central obesity predisposes to airway closure during bronchoconstriction. Issue 6 (29th January 2019) - Peters, Ubong; Subramanian, Meenakumari; Chapman, David G.; Kaminsky, David A.; Irvin, Charles G.; Wise, Robert A.; Skloot, Gwen S.; Bates, Jason H.T.; Dixon, Anne E.
ABSTRACT: Background and objective: Obesity produces restrictive effects on lung function. We previously reported that obese patients with asthma exhibit a propensity towards small airway closure during methacholine challenge which improved with weight loss. We hypothesized that increased abdominal adiposity, a key contributor to the restrictive effects of obesity on the lung, mediates this response. This study investigates the effect of body mass index (BMI) versus waist circumference (WC) on spirometric lung function, sensitivity to airway narrowing and closure, and airway closure during bronchoconstriction in patients with asthma. Methods: Participants underwent spirometry and methacholine challenge. Sensitivity to airway closure and narrowing was assessed from the dose–response slopes of the forced vital capacity (FVC) and the ratio of forced expiratory volume in 1 s (FEV1 ) to FVC, respectively. Airway closure during bronchoconstriction (closing index) was computed as the percent reduction in FVC divided by the percent reduction in FEV1 at maximal bronchoconstriction. Results: A total of 116 asthmatic patients (56 obese) underwent methacholine challenge. Spirometric lung function was inversely related to WC ( P < 0.05), rather than BMI. Closing index increased significantly during bronchoconstriction in obese patients and was related to increasing BMI ( P = 0.01), but not to WC. Sensitivity to airway closure and narrowing was not associated with BMI or WC. Conclusion: Although WC is associated with restrictive effects on baseline lung function, increased BMI, rather than WC, predisposes to airway closure during bronchoconstriction. These findings suggest that obesity predisposes to airway closure during bronchoconstriction through mechanisms other than simple mass loading. Abstract : The effect of body mass index (BMI) and waist circumference (WC) on spirometric lung function and airway closure during induced bronchoconstriction was assessed in patients with asthma. WC, but not BMI, was associated with restrictive effects on baseline spirometry. However, during bronchoconstriction, airway closure was associated with increased BMI, rather than WC. See related Editorial